2004
DOI: 10.1074/jbc.m400402200
|View full text |Cite
|
Sign up to set email alerts
|

Destabilization of the Colicin E9 Endonuclease Domain by Interaction with Negatively Charged Phospholipids

Abstract: We have shown previously that the 134-residue endonuclease domain of the bacterial cytotoxin colicin E9 (E9 DNase) forms channels in planar lipid bilayers (Mosbahi, K., Lemaître, C., Keeble, A. H., Mobasheri, H., Morel, B., James, R., Moore, G. R., Lea, E. J., and Kleanthous, C. (2002) Nat. Struct. Biol. 9, 476 -484). It was proposed that the E9 DNase mediates its own translocation across the cytoplasmic membrane and that the formation of ion channels is essential to this process. Here we describe changes to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
31
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(37 citation statements)
references
References 33 publications
6
31
0
Order By: Relevance
“…This lipid-induced destabilization was also observed in thermal unfolding experiments followed by CD in the far-UV region (12). Such a loss of cooperativity upon diC8PI binding is characteristic of membrane-bound proteins lacking tertiary structure interactions (17,18). In line with these results, limited proteolysis experiments in the presence of diC8PI micelles or anionic SUVs increased the susceptibility of PimA to proteolysis (12).…”
Section: Figure 1 Biosynthesis Of Pims In Mycobacteriasupporting
confidence: 74%
See 1 more Smart Citation
“…This lipid-induced destabilization was also observed in thermal unfolding experiments followed by CD in the far-UV region (12). Such a loss of cooperativity upon diC8PI binding is characteristic of membrane-bound proteins lacking tertiary structure interactions (17,18). In line with these results, limited proteolysis experiments in the presence of diC8PI micelles or anionic SUVs increased the susceptibility of PimA to proteolysis (12).…”
Section: Figure 1 Biosynthesis Of Pims In Mycobacteriasupporting
confidence: 74%
“…Such a loss of cooperativity upon binding of PI or DOPG liposomes is characteristic of membrane-bound proteins in molten globule-like (MG-like) states, i.e. displaying native-like secondary structures but lacking a stable tertiary structure (17,18,21).…”
Section: Anionic Phospholipids Selectively Trigger a Conformationalmentioning
confidence: 99%
“…The presence of an unstructured terminal tail of membrane substrates that penetrate into the cytoplasm appears to be important in initiating FtsH-de- pendent proteolysis (48). It is conceivable that DNase colicins have a similar access to FtsH, because their nuclease domain exhibits an endogenous channel-forming activity, possibly allowing its self-propulsion into the cytoplasm (14,15). An electrostatically mediated interaction of the nuclease domain of E type colicins with the inner membrane has been reported (16).…”
Section: Discussionmentioning
confidence: 99%
“…The DNase domains of colicins E9 and E2 exhibit nonvoltage-gated channel forming activity in planar lipid bilayers, which involves changes in their conformation (14). Such channels, unlike those formed by pore-forming colicins, are not directly responsible for cell killing but may allow "self-propulsion" of the toxic domains into cytoplasm, driven by an electrostatic association of the DNase domain of colicin E9 with the inner membrane (15). Although such an association between the RNase colicin E3 and anionic phospholipid surfaces has been reported, no RNase colicin has been found to exhibit any channel forming activity (16).…”
mentioning
confidence: 99%
“…Dover et al suggested that the poreforming domain of colicin N might translocate through OmpF, following the same route as the N-terminal domain (161). Alternatively, the C-terminal domain might translocate through the OM bilayer by conformational changes induced by its interaction with the phospholipids (468,469,470) or at the interface between the porin trimer and the LPS leaflet. It has also been proposed that for group A colicins, interactions between the colicin N-terminal domain and the Tol machinery would displace Tol-Tol interactions (such as the TolB-Pal complex) (417) and then induce an OM defect and the subsequent entry of the cytotoxic domain (147).…”
Section: Speculative Models For Colicin Translocationmentioning
confidence: 99%